Pengaruh Kualitas Produk, Citra Merek dan Iklan Terhadap Keputusan Pembelian Kartu XL Prabayar di Kota Semarang (Studi Kasus pada Pengguna Kartu XL Prabayar di Kota Semarang) - Triastuti Ayuningtias; Handoyo Djoko Waluyo (Jurnal Ilmu Administrasi Bisnis, 2017)
This research aims to know the influence of product quality, brand image and advertising against the decision of purchase cards XL prepaid. This research type is eksplanatory research. The population was XL card Prepaid users in the city of Semarang. Sample research as much as 100 respondents. The sampling technique used was accidental sampling and purposive sampling. The scale of measurement using the Likert scale. Methods of data analysis used was the validity, reliability, cross-tabulations, correlation, linear regression, the determination of the coefficient of simple linear regression, double, t and f tests using SPPS program for Windows version 16.0. Based on the research results show that the quality of the products have an effect on purchasing decisions of 0.544. Brand image effect on purchasing decisions of 0.625. The advertisement influence on purchasing decisions of 0.591. Product quality, brand image and ads simultaneously influence on purchasing decisions with the regression coefficients of the product quality of 0.325, brand image of 0.242 and advertising of 0.189.